The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40268-015-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Activated Factor VII Significantly Reduces Transfusion Requirements in Cardiothoracic Surgery

Abstract: BackgroundThe off-label use of recombinant activated factor VII (rFVIIa) for intractable bleeding is associated with a risk of thrombotic events. The objective of this study was to evaluate the incidence and predictors of rFVIIa-related thrombotic events and its efficacy in the reduction of transfusion requirements during various surgeries.MethodsNinety-two cases received rFVIIa for uncontrollable bleeding despite medical and surgical hemostasis. The incidence and risk factors of thrombotic events were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(25 reference statements)
1
7
0
1
Order By: Relevance
“…A number of previously published reports have suggested that rFVIIa is appropriate for rescue therapy of massive bleeding in cardiovascular surgery patients. 9,[20][21][22][23][24][25][26][27][28][29] The NYULH off-label guideline recommends a dose of 20 µg/kg for this indication, followed by repeat dosing of 20 µg/kg to a maximum cumulative dose of 80 µg/kg if needed. This recommendation was implemented in order to mitigate potential harm associated with the use of rFVIIa, without compromising efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previously published reports have suggested that rFVIIa is appropriate for rescue therapy of massive bleeding in cardiovascular surgery patients. 9,[20][21][22][23][24][25][26][27][28][29] The NYULH off-label guideline recommends a dose of 20 µg/kg for this indication, followed by repeat dosing of 20 µg/kg to a maximum cumulative dose of 80 µg/kg if needed. This recommendation was implemented in order to mitigate potential harm associated with the use of rFVIIa, without compromising efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have used higher doses in this patient population, the antithrombotic therapy oversight group along with cardiac surgery at NYULH recommended a lower initial dose, with the ability to repeat dosing if refractory bleeding persisted. 6,9,20,29 In our evaluation, 77% of doses were according to the NYULH guideline, 4% All values expressed as n (%). One patient had both an ischemic and hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Omar et al . [ 30 ] conducted a subgroup analysis for a group of patients received rFVIIa for uncontrolled bleeding. He showed that cardiothoracic surgery subgroup had 4.3% thrombotic events.…”
Section: Discussionmentioning
confidence: 99%
“…A second study in 70 patients undergoing cardiothoracic surgery found that rFVIIa significantly reduced blood component transfusions postadministration, with 9.8% of patients suffering thromboembolic events. 31 A third single-center experience in 144 complex cardiac surgery patients matched with 359 control patients reported a significant increase in mortality associated with perioperative use of rFVIIa (40 vs. 18%, respectively). 32 In pediatric patients, a single randomized trial was conducted to assess the benefit of prophylactic rFVIIa during and after surgical correction of congenital heart defects while on CBP.…”
Section: Cardiovascular Surgerymentioning
confidence: 99%